1984
DOI: 10.1002/anie.198409321
|View full text |Cite
|
Sign up to set email alerts
|

The Homoaldol Reaction, or How to Overcome Problems of Regio‐ and Stereo‐selectivity

Abstract: Dedicated to Professor Wolfgang Liittke on the occasion of his 65th birthdayEven today, there are conspicuous gaps in the register of organic synthetic methods. Thus, numerous types of homoenolate reagents are listed; yet no generally applicable method for the homologue of the aldol addition, viz. the homoaldol addition, is to be found. The methods documented up to 1980 offer only singular solutions, and, moreover, are not stereoselective. The present article gives an overview of the existing possibilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(56 citation statements)
references
References 194 publications
0
55
0
Order By: Relevance
“…Such as trategy is only possible if the carbanion intermediate A is configurationally stable under the reaction conditions and proceeds with complete stereocontrol of the electrophile (either pure retention or pure inversion of configuration). [3,10] As each of these isomers can react with electrophiles through four different pathways (S E ret, S E inv, syn-S' E ,a nd anti-S' E ), only the introduction of strongly complexing groups such as N,N-dialkylcarbamoyloxy [11] or N-(alkoxycarbonyl)amino [12] led to selective transformations,e ither through deprotonation of optically active secondary allyl carbamates [13] or through ad ynamic thermodynamic resolution process (Scheme 2, path B). [4,5] More recent developments have shown that few main-group organometallic species,s uch as organomagnesium [6] and organolithium, [7] as well as transition-metal species,s uch as alkylcopper [8] and alkylzinc, [9] present some configurational stability under particular circumstances (Scheme 1, path C).…”
mentioning
confidence: 99%
“…Such as trategy is only possible if the carbanion intermediate A is configurationally stable under the reaction conditions and proceeds with complete stereocontrol of the electrophile (either pure retention or pure inversion of configuration). [3,10] As each of these isomers can react with electrophiles through four different pathways (S E ret, S E inv, syn-S' E ,a nd anti-S' E ), only the introduction of strongly complexing groups such as N,N-dialkylcarbamoyloxy [11] or N-(alkoxycarbonyl)amino [12] led to selective transformations,e ither through deprotonation of optically active secondary allyl carbamates [13] or through ad ynamic thermodynamic resolution process (Scheme 2, path B). [4,5] More recent developments have shown that few main-group organometallic species,s uch as organomagnesium [6] and organolithium, [7] as well as transition-metal species,s uch as alkylcopper [8] and alkylzinc, [9] present some configurational stability under particular circumstances (Scheme 1, path C).…”
mentioning
confidence: 99%
“…49 The Knovenagel condensation has been carried out diastereoselectively 50 ' 51 and enantioselectively. 52 ' 53 Dilithio Nmethaiesulfinyl-p-toluidine, 5 4 tosylmethylisocyanide 5 5 , a-methoxyvinyllithium, 5 6 lithiated allylic carbamate, 57 and lithium bis(ethylenedioxyboryl)methide 58 have been employed as catalysts in the modified version of this reaction. Recently, antimony based in situ generated catalysts have been used to successfully alkylidenate steroidal ketones.…”
Section: Resultsmentioning
confidence: 99%
“…[4] More recently Fu [8a] reported amechanistically related NHC catalyzed cyclization of 3 via the homoenolate 4a, [9] itself formed through 1,4addition and tautomerization, to give the cyclopentane 5 [Eq. (2)]. Anorthogonal approach to homoenolates,exploit-ing the more conventional 1,2-addition of NHCs to a,bunsaturated aldehydes (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…[1] Their reactions,m ost commonly 1,4-additions with nucleophiles,p roceed in ap redictable fashion, allowing reliable use in target-focused studies.Inverting the polarity of conjugate acceptors gives nucleophiles b to the electronwithdrawing group,h omoenolates. [2][3][4] While synthesis by stoichiometric generation of homoenolates has received attention for more than 50 years, [2] catalytic approaches have appeared more intermittently. [3,4] As part of ongoing studies on the umpolung of conjugate acceptors, [5,6] herein we report N-heterocyclic carbene (NHC) catalyzed [7] all-carbon (5+ +1) annulations by ah itherto unreported vinyl dianion synthon strategy.S pecifically, b-unsubstituted conjugate acceptors undergo homoenolate formation twice and couple to fivecarbon bis(electrophile)s to provide mono-and bicyclic cyclohexanones.T he reaction has been realized with inter-and intramolecular designs,a nd in some cases,w ith high levels of enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%